2006
DOI: 10.1039/b608364a
|View full text |Cite
|
Sign up to set email alerts
|

Fast and “green” living cationic ring opening polymerization of 2-ethyl-2-oxazoline in ionic liquids under microwave irradiation

Abstract: The living cationic ring opening polymerization of 2-ethyl-2-oxazoline performed in an ionic liquid under microwave irradiation showed an enhanced polymerization rate in comparison to the reaction in common organic solvents; the ionic liquid was efficiently recovered and reused in new reaction cycles, completely avoiding the use of organic volatile compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 17 publications
1
61
0
1
Order By: Relevance
“…In an alternate analysis approach to the study of potential 2Ј-deoxycytidine deamination, 2Ј-deoxycytidinecontaining ODNs (10#5, 5#1, 5#6-5#14, Table 1) prepared by microwave-assisted deprotection were enzymatically hydrolyzed to mononucleosides by a combination of snake venom phosphodiesterase I (Crotalus adamanteus) (Williams et al, 1961;Bowman et al, 2001) and alkaline phosphatase (E. coli) (Reid and Wilson, 1971;McComb et al, 1979;Chandrasegaran et al, 1985;Marguet and Forterre, 2001;Gasan et al, 2002;Guerrero-Sanchez et al, 2006). Differential elution of the resultant mononucleosides by RP-HPLC was observed by UV-detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an alternate analysis approach to the study of potential 2Ј-deoxycytidine deamination, 2Ј-deoxycytidinecontaining ODNs (10#5, 5#1, 5#6-5#14, Table 1) prepared by microwave-assisted deprotection were enzymatically hydrolyzed to mononucleosides by a combination of snake venom phosphodiesterase I (Crotalus adamanteus) (Williams et al, 1961;Bowman et al, 2001) and alkaline phosphatase (E. coli) (Reid and Wilson, 1971;McComb et al, 1979;Chandrasegaran et al, 1985;Marguet and Forterre, 2001;Gasan et al, 2002;Guerrero-Sanchez et al, 2006). Differential elution of the resultant mononucleosides by RP-HPLC was observed by UV-detection.…”
Section: Resultsmentioning
confidence: 99%
“…This contrasts with the fully labile N-protective strategy (dA PAC , dC ibu , dG PAC ) when using 1 M NaOH demonstrated by Kumar Gupta (1997, 1999a, 1999b or the use of dC Ac by Reddy et al (1994Reddy et al ( , 1995Reddy et al ( , 1997 making our procedure more attractive for library production. Interestingly, Guerrero-Sanchez et al (2006) have demonstrated the stability of CPG support material under more intense microwave irradiation (800 W).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that microwave heating accelerates hydrolysis of cellulose in 1.0 M acidic IL, 1-(1-butylsulfonic)-3-methylimidazolium hydrogen sulfate ([Sbmim][HSO4]; Figure 1) [22], because the combination of ILs and microwave is known to exert synergistic effects on several reactions [23][24][25]. In the literature, the glucose yield has increased from a few percent after 30 min to 40% after 12 min at 160 °C when using microwave irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the utilization of ionic liquids (ILs) as new solvents [1][2][3][4][5][6][7][8][9] for the preparation of self-assembled nanostructures (micelles) formed by amphiphilic block copolymers has triggered attractive new possibilities for the design of advanced and ''smart'' polymer based physico-chemical systems. [10][11][12][13][14][15][16][17][18][19][20][21] Interestingly, the thermoreversible transfer of block copolymer micelles and nanocarriers between a hydrophobic IL phase and an aqueous phase was recently demonstrated based on the decreased solubility of the hydrophilic block in aqueous solution with increasing temperature.…”
Section: Introductionmentioning
confidence: 99%